Manajemen Perubahan Dalam Menciptakan Mahasiswa Yang Berakhlakul Karimah - Musyafa, Muhammad Helma (Transformasi Manageria Journal of Islamic Education Management, 2024)
Judging from the lack of good behavior in students, this is a negative perspective. Therefore, as a student, I also really feel that this is inappropriate for a student to do, especially at an Islamic university. Changing behavior to be more polite and good in Islam is a moral value. Akhlakul Karimah itself is a benchmark for example behavior for Muslims and Muslimat. Which, as exemplified by the Prophet Muhammad as uswatun hasanah, where the Apostle was very careful in behaving, in speaking and even being careful when determining Islamic law which he carried out with his friends. It is appropriate for us as people to follow what the apostle taught, said, and commanded us to immediately implement and apply to our daily lives. Therefore change management is needed so that how management can enter to change for the better of students, which is for the sake of realizing the practice of akhlakul karimah. Keywords : change management, student behavior, akhlakul karimah.